Some Medicinal Ferns from Western India - Puri, G. S.; Arora, R. K. (Indian Forester, 1961)
The medicinal fern-flora of Western India is dealt with. Descriptive notes based on herbarium sheets have been given along with the medicinal uses of the plants. The article mainly intends to give information on the areas of distribution.